Exploration of Bibliometric Research in Accounting Information: Trends and Challenges - Siska Aprianti; Sulaiman Efendi Siregar; Loso Judijanto; Indah Wati (Westscience Press, 2023)
This paper explores the changing environment of research trends and problems in accounting information through a thorough bibliometric analysis. With the aid of sophisticated visualization tools such as Vosviewer and the databases Scopus and Web of Science, we examine a selected dataset of academic papers from 1963 to 2023. Within the domain, our analysis reveals topic clusters, keyword occurrences, collaborative networks, and influential works. Interdisciplinarity is highlighted by collaborative networks, which highlight the increasing convergence of accounting, finance, economics, and technology. Citation analysis identifies important works that have influenced the subject and provides insights into long-lasting contributions. Thematic clusters offer academics a way to navigate a variety of study frontiers, from the complex relationships between accounting standards and the capital market to the revolutionary impact of technology. The continuous emphasis on accounting information systems is highlighted by keyword occurrence analysis, which also reveals new themes like big data and the internet. The amalgamation of these discoveries functions as a guide for academics, professionals, and decision-makers, directing forthcoming research projects towards domains of importance, novelty, and cross-disciplinary investigation.